Solventless type coating agent

JP2025029329APending Publication Date: 2025-03-06AICA KOGYO CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023133879
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-21
Publication Date
2025-03-06

AI Technical Summary

Benefits of technology

【0011】 本発明の無溶剤型コーティング剤は、ポリ塩化ビニル製基材と十分な密着性を有すると同時に、良好な耐ヒールマーク性を有し、また裁断加工性が良好でカットする際に割れが生じ難いため、塩ビタイルのような床材に用いるコーティング剤として有用である。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025029329000001
    Figure 2025029329000001
  • Figure 2025029329000002
    Figure 2025029329000002
  • Figure 2025029329000003
    Figure 2025029329000003
Patent Text Reader

Abstract

To provide a solventless type coating agent for a polyvinyl chloride-made base material which has good cutting workability and prevents cracking at the time of cutting, while having good heel mark resistance.SOLUTION: A solventless type coating agent for a polyvinyl chloride-made base material contains polyfunctional urethane (meth)acrylate, a phosphate compound, a reactive diluent, and a photopolymerization initiator, wherein storage elastic modulus at 40°C of its cured product is 230 MPa or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a solventless coating for use on polyvinyl chloride substrates. [Background technology]

[0002] Plastic flooring materials are used in a wide range of buildings, from office buildings and commercial facilities to ordinary homes. Among these plastic flooring materials, vinyl resin flooring materials, including polyvinyl chloride, are relatively inexpensive and easy to install, and have many excellent properties such as chemical resistance, abrasion resistance, scratch resistance, flexibility, and ability to conform to the substrate, so they are used in a wide range of places, including schools, hospitals, factories, and government facilities.

[0003] For example, vinyl tiles are a typical example of vinyl flooring. While cushioned flooring, which is also made of polyvinyl chloride, is soft and not very durable, and is easily dented or worn down by the legs of tables and chairs, vinyl tiles have a moderate hardness and durability. They are also cheaper and easier to install than wooden or ceramic flooring materials, and can be made thinner than these, so they have the advantage of not interfering with door opening and closing or thresholds even when installed directly on existing flooring.

[0004] Due to these advantages, PVC tiles are used in a wide range of fields. On the other hand, although they are relatively hard, their surfaces are easily scratched and worn, so that they are often coated with a coating agent that improves their resistance to scratches and heel marks. For example, PVC tiles that form a glassy inorganic protective coating layer on their surface have been proposed (Patent Document 1). However, the harder the coating layer, the lower the cutting processability when processing into a tile shape, and the more likely it is to crack. Therefore, there has been a demand for a well-balanced coating agent that has sufficient resistance to scratches and heel marks, while at the same time causing very little cracking of the coating layer when cutting. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent No. 6065247 Summary of the Invention [Problem to be solved by the invention]

[0006] An object of the present invention is to provide a solventless coating agent for polyvinyl chloride substrates which has good heel mark resistance, good cutting processability and is less likely to crack when cut. [Means for solving the problem]

[0007] In order to solve the above problems, the invention described in claim 1 provides a solventless coating agent for polyvinyl chloride substrates, which is a photocurable resin composition containing a multifunctional urethane (meth)acrylate (A), a phosphate ester compound (B), a reactive diluent (C), and a photopolymerization initiator (D), and is characterized in that the storage modulus of the cured product is 230 MPa or less at 40°C.

[0008] The invention according to claim 2 provides the solventless coating agent for polyvinyl chloride substrates according to claim 1, characterized in that the weight average molecular weight of (A) is 3,000 to 30,000.

[0009] The invention as set forth in claim 3 provides the solventless coating agent for polyvinyl chloride substrates as set forth in claim 1, further comprising a silicone-modified (meth)acrylate monomer (E).

[0010] The invention according to claim 4 provides a building material coated with the solventless coating agent for polyvinyl chloride substrates according to any one of claims 1 to 3. Effect of the Invention

[0011] The solvent-free coating agent of the present invention has sufficient adhesion to polyvinyl chloride substrates, and at the same time has good heel mark resistance. It also has good cutting processability and is less likely to crack when cut, making it useful as a coating agent for floor materials such as PVC tiles. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The present invention will be described in detail below.

[0013] The solvent-free coating agent of the present invention is composed of a polyfunctional urethane (meth)acrylate (A), a phosphoric acid ester compound (B), a reactive diluent (C), and a photopolymerization initiator (D). In this specification, the term "(meth)acrylate" includes both acrylate and methacrylate.

[0014] The polyfunctional urethane (meth)acrylate (A) used in the present invention is one of the main components constituting the cured film, and has abrasion resistance and toughness due to the cohesive force of hydrogen bonds derived from urethane bonds. The number of functional groups is preferably 2 to 8, more preferably 4 to 6. By making it 2 or more functional, sufficient curability and adhesion to the adherend can be ensured, and by making it 8 or less functional, the storage modulus can be kept low and cutting processability can be sufficiently stabilized. In addition, when it has a polyester-modified skeleton, it is preferable because it can further improve heel mark resistance.

[0015] The (A) is preferably an allophanate-based urethane (meth)acrylate having an allophanate bond (-NH-CO-NCOO- group) in which a urethane bond has reacted with an isocyanate group. In an allophanate-based urethane (meth)acrylate, the interaction of hydrogen bonds between OH groups, which has a large effect on viscosity, is intramolecular, so that it is possible to lower the viscosity and the cure shrinkage is likely to be small compared to a urethane (meth)acrylate of the same structure that does not have an allophanate bond. In addition, it has good curability with a fast cure speed and little stickiness, and the storage modulus tends to be kept low.

[0016] The weight molecular weight (hereinafter referred to as Mw) of (A) is preferably 3,000 to 30,000, more preferably 4,000 to 15,000, and particularly preferably 5,000 to 10,000. By making it 3,000 or more, the increase in storage modulus can be sufficiently suppressed, and by making it 30,000 or less, the composition viscosity can be easily adjusted to a suitable level for workability. Note that Mw was measured and calculated by gel permeation chromatography using a column with a styrene-divinylbenzene-based packing material and a tetrahydrofuran eluent as the molecular weight in terms of standard polystyrene.

[0017] The blending amount of the (A) is preferably 30 to 60% by weight, more preferably 35 to 55% by weight, and particularly preferably 40 to 50% by weight, based on the total solid content. By making it 30% by weight or more, sufficient cutting processability can be ensured, and by making it 60% by weight or less, it becomes easy to adjust the viscosity to be suitable for application, and sufficient leveling property can also be ensured.

[0018] The phosphoric acid ester compound (B) used in the present invention is blended for the purpose of improving the adhesive strength with the substrate. A (meth)acrylate monomer having a phosphoric acid ester group is preferable in terms of compatibility with (A) and excellent curing properties. For example, 2-(meth)acryloyloxyethyl dihydrophosphate, dipentaerythritol penta(meth)acryloyloxydihydrogen phosphate, etc. are included. In particular, bis[2-(methacryloyloxy)ethyl] hydrogen phosphate of the following chemical formula (1), which is generated by the reaction of 2-hydroxyethyl methacrylate with phosphoric anhydride, is preferable. Chemical formula (1) JPEG2025029329000001.jpg3355

[0019] The amount of (B) is preferably 0.3 to 5.0% by weight, more preferably 0.5 to 3.0% by weight, based on the total solid content. By adding it in this range, the adhesive strength with the substrate can be improved. Commercially available (meth)acrylate monomers having a phosphate ester group include KAYAMER PM-2 and PM-21 (trade names: manufactured by Nippon Kayaku Co., Ltd.).

[0020] The reactive diluent (C) used in the present invention is blended for the purpose of lowering the viscosity of the composition and improving the curing property. In order to keep the storage modulus low, it is preferably trifunctional or less, and more preferably monofunctional. For example, examples of the chain alkyl monomer include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, hexyl (meth)acrylate, octyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate, examples of the alicyclic monomer include cyclohexyl (meth)acrylate and isobornyl (meth)acrylate, examples of the monomer having a hydroxyl group include 2-hydroxyethyl (meth)acrylate, 3-hydroxyethyl (meth)acrylate, and 4-hydroxyethyl (meth)acrylate. Examples of the monomers having an aromatic ring include benzyl (meth)acrylate, phenoxyethyl acrylate, and methylphenoxyethyl acrylate. Examples of the amide compounds include N,N-dimethyl (meth)acrylamide, N,N-diethyl (meth)acrylamide, and acryloylmorpholine. These can be used alone or in combination of two or more. Among these, hydroxyl group-containing (meth)acrylates are preferred in terms of improving adhesion to vinyl chloride, and 2-hydroxypropyl methacrylate, which has good compatibility with (A) and (B) and is highly dilutable, is even more preferred.

[0021] The amount of (C) is preferably 10 to 50% by weight, more preferably 20 to 40% by weight, and particularly preferably 25 to 35% by weight, based on the total solid content. By making it 10% by weight or more, it is possible to expect adjustment to a viscosity with excellent workability and at the same time ensure sufficient curing properties, and by making it 50% by weight or less, it is possible to keep the storage modulus low and ensure good cutting processability.

[0022] The photopolymerization initiator (D) used in the present invention generates radicals when irradiated with ultraviolet light or an electron beam, and the radicals trigger the polymerization reaction, and general-purpose photopolymerization initiators such as benzyl ketal, acetophenone, and phosphine oxide photopolymerization initiators can be used. By arbitrarily selecting the light absorption wavelength of the polymerization initiator, it is possible to impart curability over a wide wavelength range from the ultraviolet region to the visible light region. Specifically, 2.2-dimethoxy-1.2-diphenylethan-1-one is a benzyl ketal, 1-hydroxy-cyclohexyl-phenyl-ketone and 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one are α-hydroxyacetophenones, 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one are α-aminoacetophenones, and 2.4.6-trimethylbenzoyl-diphenyl-phosphine oxide and bis(2.4.6-trimethylbenzoyl)-phenylphosphine oxide are acylphosphine oxides, which may be used alone or in combination of two or more. Among these, it is preferable to use α-hydroxyacetophenones, which are less prone to yellowing.

[0023] The amount of (D) is preferably 2 to 15 parts by weight, more preferably 5 to 10 parts by weight, per 100 parts by weight of the photopolymerizable component. By adding 2 parts by weight or more, sufficient curability can be ensured, and by adding 15 parts by weight or less, an excessive amount is not added, and sufficient molecular weight can be ensured even after curing. Commercially available α-hydroxyacetophenone products include JRCURE1103 (trade name: manufactured by Daido Chemical Industry Co., Ltd.).

[0024] In the present invention, it is preferable to further contain a silicone-modified (meth)acrylate monomer (E). By blending (E), heel mark resistance can be stably improved. For example, urethane (meth)acrylate having a silicone skeleton can be mentioned. The Mw of (E) is preferably 1,000 to 20,000, more preferably 3,000 to 15,000. By setting it in this range, heel mark resistance can be sufficiently improved.

[0025] The amount of (E) is preferably 30% by weight or less, more preferably 20% by weight or less, and particularly preferably 15% by weight or less, based on the total solid content of the composition. By making it 30% by weight or less, it is possible to improve heel mark resistance and cutting processability in a well-balanced manner.

[0026] In addition, additives such as leveling agents, inorganic fillers, surfactants, tackifiers, antioxidants, ultraviolet absorbers, flame retardants, defoamers, wettability adjusters, organic fine particles, and antistatic agents can be used in combination with the solventless coating agent of the present invention (hereinafter referred to as the present coating agent) within a range that does not impair the performance.

[0027] The leveling agent can improve the leveling properties during coating and can also improve the scratch resistance and stain resistance of the cured coating. Examples of the leveling agent include fluorine-based, silicone-based, and fluorine silicone-based agents, and can be used alone or in combination of two or more types.

[0028] Among these, silicone-based polysiloxane compounds that can equalize the large surface tension difference on the coating film surface are preferred. Examples include polyalkyl siloxanes, polyaryl siloxanes, polyalkylaryl siloxanes, polyester-modified siloxanes, polyether-modified siloxanes, etc., which can be used alone or in combination of two or more kinds.

[0029] The amount of the leveling agent is preferably 0.1 to 3% by weight, more preferably 0.3 to 2% by weight, based on the total solid content. By setting the amount within this range, sufficient leveling properties can be ensured, and the coating film can have a stable appearance, while improving scratch resistance and antifouling properties. Commercially available products include TEGO Glide 410 (trade name: polyether-modified siloxane copolymer, manufactured by EVONIK INDUSTRIES).

[0030] The inorganic filler can improve the appearance of the coating film and the hardness of the cured coating film. Examples of the inorganic filler include silica particles, alumina particles, and titanium oxide particles, and can be used alone or in combination of two or more kinds. By blending the component, light is diffusely reflected, and the gloss of the coating film surface can be suppressed. In addition, in order to improve adhesion to the coating film, it is preferable to treat the surface with an organic component.

[0031] In particular, when adjusting the glossiness of the coating film appearance, it is preferable to blend amorphous silica with a secondary particle size of 0.5 to 10 μm. Also, by blending silica with a polyethylene-treated surface, a very smooth matte surface can be obtained. The blending amount depends on the desired glossiness, but for example, 1 to 20% by weight based on the total solid content is exemplified. Commercially available products include ACEMATT OK607 (trade name: manufactured by EVONIK INDUSTRIES, secondary particle size 4.4 μm, surface polyethylene-treated), etc.

[0032] This coating agent is applied to polyvinyl chloride substrates. For example, when used as a coating agent for the surface of polyvinyl chloride tiles, it is suitable because it has excellent heel mark resistance and the coating film is less likely to crack during cutting. In the present invention, "solvent-free" means that a solvent is not intentionally blended for the purpose of dilution, and does not mean that even volatile components contained in small amounts in each component of the composition are excluded, and the solvent content is 5% by weight or less, typically 1% by weight or less.

[0033] The method for applying the coating agent is not particularly limited and may be any known method. When applying to the entire surface of an adherend, for example, a roll coater, a reverse roll coater, a knife coater, an air knife coater, a bar coater, a slot die coater, a lip coater, a gravure coater, a reverse gravure coater, etc. may be used.

[0034] After being applied to a substrate, the coating agent is cured using light such as ultraviolet light. Examples of light sources include low-pressure mercury lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, carbon arc lamps, xenon lamps, metal halide lamps, LED lamps, and electrodeless ultraviolet lamps. The curing conditions are 50 mW / cm. 2 ~3000mW / cm 2 The irradiation intensity is 100 to 2,000 mJ / cm2 as the cumulative light quantity. 2 The irradiation atmosphere may be air or an inert gas such as nitrogen or argon.

[0035] The softening point of the polyvinyl chloride substrate to which this coating agent is applied is around 65°C, but if it contains a plasticizer, the softening point drops further. When cutting polyvinyl chloride tiles containing plasticizers, they may be heated, and if the storage modulus of the coating agent is relatively high compared to the polyvinyl chloride tile that is softening due to the plasticizer and heat, cracks tend to easily appear in the coating film near the cut area.

[0036] Therefore, the storage modulus of the cured product obtained by photocuring this coating agent is 230 MPa or less at 40°C, and more preferably 150 MPa or less. The storage modulus at 30°C is preferably 600 MPa or less, and more preferably 250 MPa or less. If it exceeds 230 MPa at 40°C, it tends to be difficult to ensure stable cutting processability. Furthermore, by setting it to 600 MPa or less at 30°C, sufficiently stable cutting processability can be ensured.

[0037] The present invention will be described in detail below based on examples and comparative examples, but these are specific examples and are not intended to be limiting. Unless otherwise specified, measurements were performed under conditions of room temperature of 25°C and relative humidity of 65%. The blend amounts are in parts by weight.

[0038] Examples 1 to 7 As (A), UreaC 1 (pentafunctional allophanate type polyester modified urethane acrylate, Mw 8,000, solid content 100%), UreaC 2 (pentafunctional allophanate type urethane acrylate, Mw 7,000, solid content 100%), and UreaC A (bifunctional polytetramethylene glycol skeleton urethane acrylate, Mw 2,500, solid content 100%) were used; as (B), KAYAMER PM-2 (trade name: manufactured by Nippon Kayaku Co., Ltd.) was used; as (C), Light Ester HOP(N) (trade name: manufactured by Kyoeisha Chemical Co., Ltd., hydroxypropyl methacrylate) was used; as (D), JRCURE1103 (trade name: manufactured by Daido Kasei Co., Ltd., α-hydroxyacetophenone type) was used; as (E), MIRAMER SIU2400 (trade name: manufactured by MIWON Co., Ltd., 10-functional silicone urethane acrylate, Mw 8,000, solid content 100%) was used; and as a leveling agent, TEGOGlide The photocurable resin compositions (solventless) of Examples 1 to 7 were prepared by mixing ACEMATT OK607 (product name: EVONIK INDUSTRIES, polyether-modified siloxane copolymer, solid content 100%) and ACEMATT OK607 (product name: EVONIK INDUSTRIES, amorphous silica with secondary particle diameter of 4.4 μm, surface-treated with polyethylene) as a filler in the formulation shown in Table 1 until uniformly dissolved.

[0039] Comparative Examples 1 to 4 In addition to the materials used in Example 1, UreaC B (difunctional caprolactone-based urethane acrylate, Mw 2,000, solids 100%) and UreaC C (trifunctional allophanate-type aliphatic urethane acrylate, Mw 1,300, solids 100%) were used as oligomers and stirred until uniformly dissolved in the formulation shown in Table 2 to prepare photocurable resin compositions (solventless) for Comparative Examples 1 to 4.

[0040] Table 1 JPEG2025029329000002.jpg114163

[0041] Table 2 JPEG2025029329000003.jpg136133

[0042] The evaluation method was as follows.

[0043] Curing: The photocurable resin composition was applied to an unpainted PVC tile with a thickness of 3 mm to a film thickness of 20 μm, and the composition was irradiated with an electrode high-pressure mercury lamp (product name: iGrandage ECS4011GX / N, manufactured by iGraphics Co., Ltd.) at an irradiation intensity of 100 mW / cm 2 , cumulative light intensity 800mJ / cm 2 The coating film was irradiated with ultraviolet light at 400 nm and the tackiness of the coating film surface was checked. Those that were cured without tackiness were rated as ◯, and those that were tacky but not cured were rated as x.

[0044] Adhesion: According to JIS K5600-5-6, a 10x10 grid of 1mm squares was created and a cross-cut test was performed, and the peeling state of the coating film was confirmed using cellophane tape (specified in JIS Z1522). When the cellophane tape attached to the coating film side was peeled off, if 0 squares peeled off, it was marked as ○, and if even 1 square peeled off, it was marked as ×.

[0045] Glossiness: According to JIS Z 8741, the 60° glossiness was measured using Micro Trigloss (manufactured by Byk-Gardner Co., Ltd.).

[0046] Heel mark resistance: Using a heel mark tester conforming to JIS K3920, six standard rubber blocks were used, and the test was run for 3,000 revolutions at 50 revolutions per minute to evaluate the initial adhesion of heel marks and their removability. The evaluation method for initial adhesion was as follows: ◎ if there were almost no adhesion marks, ◯ if there were slight adhesion marks, and × if there were dark adhesion marks. Regarding dirt removability, ◎ if the adhesion marks could be completely removed with a cloth, ◯ if there were slight adhesion marks remaining, and × if they could not be removed at all.

[0047] Cutting processability: The coating was applied to an unpainted PVC tile with a thickness of 3 mm so that the dry film thickness was 20 μm, and the coating was applied using an electrode high-pressure mercury lamp (product name: iGrandage ECS4011GX / N, manufactured by iGraphics Co., Ltd.) with an irradiation intensity of 100 mW / cm 2 , cumulative light intensity 800mJ / cm 2The test specimen was then returned to room temperature and placed in a 40°C thermostatic chamber for at least 3 hours, after which it was punched out using a No. 3 dumbbell from the test specimen heated to 40°C, and the cross section was observed under an electron microscope at 150x magnification. If no cracks were found in the coating, they were marked with an ◯, and if cracks were found, they were marked with an X.

[0048] Storage modulus: Using a TAinstruments DMAQ800, a resin composition with a width of 5 mm and a film thickness of 200 μm was cured with the above UV device under conditions of an illuminance of 100 mW / cm2 and an accumulated light quantity of 800 mJ / cm2, and the storage modulus was measured at 30°C and 40°C. The evaluation method at 30°C was as follows: 250 MPa or less was ◎, more than 250 MPa and less than 600 MPa was 〇, and more than 600 MPa was ×. At 40°C, 150 MPa or less was ◎, more than 150 MPa and less than 230 MPa was 〇, and more than 230 MPa was ×.

[0049] Table 3 JPEG2025029329000004.jpg123166

[0050] Table 4 JPEG2025029329000005.jpg138122

[0051] The resin compositions of the Examples showed good results in the evaluations of curability, adhesion, heel mark resistance, and cutting processability. In all Examples, the storage modulus was 500 MPa or less at 30°C and 200 MPa or less at 40°C.

[0052] On the other hand, Comparative Example 1, which did not contain (B), had poor adhesion, and Comparative Examples 2 to 4, which had a storage modulus at 40° C. of more than 230 MPa, had poor cutting processability, and none of them were suitable for the present invention.

Claims

1. A solventless coating agent for polyvinyl chloride substrates, comprising a photocurable resin composition comprising a multifunctional urethane (meth)acrylate (A), a phosphoric acid ester compound (B), a reactive diluent (C) and a photopolymerization initiator (D), the photocurable resin composition having a storage modulus of 230 MPa or less at 40°C.

2. 2. The solventless coating agent for polyvinyl chloride substrates according to claim 1, wherein the weight average molecular weight of (A) is 3,000 to 30,000.

3. 2. The solventless coating agent for polyvinyl chloride substrates according to claim 1, further comprising a silicone-modified (meth)acrylate monomer (E).

4. A building material coated with the solventless coating agent for polyvinyl chloride substrates according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Air-fuel ratio controlling method in internal- combustion engine

    JP1985065247A